Orthorexia nervosa predisposition and eating behaviors in hypertension patients: A case-control study - Yanmis, Safiye; Turan, Gülcan Bahçecioğlu; Özer, Zülfünaz (Yuzuncu Yil Universitesi Tip Fakultesi, 2024)
The aim of this case-control study is to evaluate whether there is a difference between individuals with hypertension and healthy individuals in terms of orthorexia nervosa and eating attitudes. This case-control study was conducted with hypertension patients (n=218) and healthy individuals (n=226) who met the research criteria in an internal medicine clinic and outpatient clinics of a university hospital between April and June 2021. The data were collected with face-to-face interview method by using ?Descriptive Information Form?, ?Orthorexia Nervosa-11 (ORTO-11) Scale? and ?Eating Attitude Scale (EAT-26)?. ORTO-11 score of HT patients was found as 26.39±4.96, while ORTO-11 score of healthy individuals was found as 27.58±4.26. EAT-26 score of HT patients was found as 9.87±7.88, while EAT-26 score of healthy individuals was found as 8.31±7.31. Statistically significant difference was found between me an ORTO-11 and EAT-26 scores of groups (p<0.05). Mean scores of 59% of HT patients and 41% of healthy individuals were found to be below ORTO-11 ? 27. Mean scores of 14.2% of HT patients and 10.1% of healthy individuals were found to be above EAT-26 ?20. In the regression analysis, EAT-26 (?=-0.401, p<0.05) variable was found to have a negative and significant effect on ORTO-11. Higher orthorexia and eating disorder risk was found in hypertension patients when compared with healthy individuals. In addition, it was found that abnormal eat ing behaviour caused individuals to show more orthorexia behaviour. © 2024, Yuzuncu Yil Universitesi Tip Fakultesi. All rights reserved.
Keywords: case-control studies; eating behaviours; eating disorders; Hypertension; orthorexia nervosa; ORTO-11